An immunohistochemical study of e-cadherin expression in primary oral squamous cell carcinoma and metastatic lymph node in a tertiary care centre - Talukdar, Leena; Goswami, Anirban (Tropical Journal of Pathology and Microbiology, 2019)
Background: Cancers arising from the oral cavity are mostly squamous cell carcinomas. E-cadherin is encoded by the CDH1 gene, helps in maintaining cell polarity and normal tissue architecture. loss of epithelial E-cadherin expression increases tumor invasiveness and metastasis. In the present study, the expression of epithelial E-cadherin in oral squamous cell carcinoma along with its grading is evaluated with immunohistochemical examination. Material and Method: Oral biopsy specimens received were fixed in 10% formaldehyde solution. Histological diagnosis was made on haematoxylin and eosin stained sections and expression of E cadherin is assessed by Immunohistochemistry. Results: In the present study out of 86 cases of OSCC, 57 were male and 29 were female with a M:F 1.9: 1. E-cadherin immunohistochemistry showed 4+ degree of expression in 15/51 (29%) cases in well differentiated carcinoma while in poorly differentiated carcinoma 4+ expression was showed only by 1/14 case. Differences in the expression of epithelial E-cadherin were statistically significant (p < 0.001) between all the histopathological grades. Any statistically significant association between the expressions of E-cadherin and clinicopathological variables such as age, sex, site and lymph node metastasis in OSCCs was not observed. Also, this study found no statistically significant association between OSCC with and without lymph node metastases and clinical variables like age, sex, site, and histological differentiation. Conclusion: Further research on E-cadherin and other related biomolecules can help us in early diagnosis and treatment of oral squamous cell carcinoma.